2022
DOI: 10.1063/10.0014014
|View full text |Cite
|
Sign up to set email alerts
|

Electron-phonon interaction and point contact enhanced superconductivity in trigonal PtBi2

Abstract: PtBi2 is a Weyl semimetal, which demonstrates superconductivity with low critical temperature Tc ∼ 0.6 K in the bulk. Here, we report our study of electron-phonon interaction (EPI) in trigonal PtBi2 by the Yanson point- contact (PC) spectroscopy and present the observation of PC enhanced superconductivity. We show that the Yanson’s PC spectra display a broad maximum around 15 meV, indicating, apparently, EPI mechanism of Cooper pairing in PtBi2. Moreover, we discovered a substantial increase of Tc up to ∼ 3.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In the context of exfoliable van der Waals materials, t-PtBi 2 is of particular interest. Beyond the very large linear magnetoresistance measured in the hexagonal and pyrite crystal structures, the spin–orbit coupling together with the broken inversion symmetry scriptI in the layered trigonal structure is responsible for a variety of interesting electronic properties, including a strong Rashba-like spin splitting, triply degenerate points in the band structure, signatures of topological edge states at single-layer steps, and pressure-induced superconductivity or under point contact measurements …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of exfoliable van der Waals materials, t-PtBi 2 is of particular interest. Beyond the very large linear magnetoresistance measured in the hexagonal and pyrite crystal structures, the spin–orbit coupling together with the broken inversion symmetry scriptI in the layered trigonal structure is responsible for a variety of interesting electronic properties, including a strong Rashba-like spin splitting, triply degenerate points in the band structure, signatures of topological edge states at single-layer steps, and pressure-induced superconductivity or under point contact measurements …”
mentioning
confidence: 99%
“…Beyond the very large linear magnetoresistance measured in the hexagonal 20 and pyrite 21 crystal structures, the spin−orbit coupling together with the broken inversion symmetry in the layered trigonal structure is responsible for a variety of interesting electronic properties, including a strong Rashba-like spin splitting, 22 triply degenerate points in the band structure, 23 signatures of topological edge states at single-layer steps, 24 and pressureinduced superconductivity 25 or under point contact measurements. 26 We calculated the electronic structure of bulk t-PtBi 2 in the space group P31m based on the crystal structure reported in ref 27. We performed fully relativistic density functional calculations treating the spin−orbit coupling in the fourcomponent formalism 28 (see section S1 of the Supporting Information for more details).…”
mentioning
confidence: 99%
“…Local enhancement of SC is observed in point-contact spectroscopy experiments on γ-PtBi 2 , reaching T c = 3.5 K and µ 0 H c2 (0) = 3 T. The origin of such effect seems to be a combination of local pressure and a change in the electron local density of states induced by the point contact [21]. More recently, two further stunning results have been disclosed in this phase.…”
Section: Introductionmentioning
confidence: 86%
“…Moreover, it was observed that the theoretical samples, in agreement with the experimental data, display the competing existence of superconducting and normal regions in them. In the presentation by Oksana Kvitnitskaya (Figure 8a) from the B. Verkin Institute for Low Temperature Physics and Engineering of the National Academy of Sciences of Ukraine in Kharkiv, trigonal PtBi 2 , a Weyl semimetal, was analyzed for electron-phonon interactions by Yanson point contact spectroscopy and a substantial increase in the T c was observed, from 0.6 K in the bulk to 3.5 K in point contacts, also indicating the electron-phonon interaction mechanism of Cooper pairing [85].…”
Section: Poster Presentationsmentioning
confidence: 99%